Study of biodiversity and limiting factors of Ag-gol Wetland in Hamadan Province, Iran (Biodiversitas Journal of Biological Diversity, 2012)
Reyahi-Khoram M, Norisharikabad V, Vafaei H. 2012. Study of biodiversity and limiting factors of Ag-gol Wetland in Hamadan Province, Iran. Biodiversitas 13: 135-139. Ag-gol Wetland isone of the important and seasonal wetlands of Iran. This wetland islocated on southeast of Hamadan Province and was declared as a prohibited hunting area by Department of Environment (DoE) of Iran. Identifying the characteristics, capabilities and limiting factors of Ag-gol Wetland is the most important objective of this study. The present study was conducted during 2007 through 2010. Documentary and observation methods have been used to access to information. For general identification of the area, digital maps and Geographic Information System (GIS) were used. Identifying capabilities and limitation factors of the studied area was made through extensive field inspections and direct field observations. Bird species of the region were identified and statistics of the population of bird species were gathered. In this research, valid academic resources were used. According to field inspections and studies, 46 species of waterfowl birds and wader birds of Iran have been identified at this wetland. The results of this research showed that Ag-gol Wetland has a high potential regarding the variety of waterfowl and wader birds. Continuous study in order to determine the depth of wetland water in different time intervals to estimate the volume of wetland water during different seasons of the year is recommended.
Keywords: biodiversity, environment, prohibited hunting area, seasonal wetland